THE RIGHT TO FREEDOM OF ASSOCIATION OF WORKERS IN THE CONSTITUTION OF THE REPUBLIC OF CUBA,2019 - Lam Peña, Reynaldo Jorge (UNIVERSIDAD DE SONORA, 2020)
This article analyzes the constitutional legal configuration of the right to freedom of association of workers in the Cuban Constitution of 2019.Part of its constitutional recognition within the right of association, a trend inherited from the countries of the Socialist Block of the XXI Century, outlining criteria around its essential content as a fundamental right and the response, of its current regulation, to face other labor rights collectives recognized in the national legal system and the constitutional guarantees of their exercise.